Agree, Move and the Scope of the Phase Impenetrability Condition - Witkoś, Jacek (Studia Anglica Posnaniensia, 2021)
This paper addresses a certain contradiction in the application of the Phase Impenetrability Condition (PIC) to domains involving the long-distance Genitive of Negation (GoN) and wh-movement in Polish. It appears that in syntactic domains of the tensed sentence including an infinitive complement, there is a tension between a long-distance dependency (holding between NEG in the main clause and the embedded object in genitive) and a cyclic operation of wh-movement. The operation of wh-movement, a classic example of Chomsky’s Move, observes cyclicity and the PIC, judging by the standard tests based on reconstruction (Chomsky 1995; Heycock 1995; Fox 1999; Safir 1999; Legate 2003; Witkoś 2003; Lebeaux 2009), while the Agree-based case marking requires the PIC to be inoperative in exactly the same context and in the same domain. Both operations place contradictory requirements on the PIC, which implies that this condition does not apply to them in the same manner: it always holds of Move but does not always hold of Agree.